1989
DOI: 10.1103/physrevd.40.4100
|View full text |Cite
|
Sign up to set email alerts
|

Muonium and positronium potentials

Abstract: Muonium and positronium potentials with radiative corrections are derived from the scattering operator, and general results for the spectra of these systems to order a 3~, are obtained. We also compare our results with those obtained earlier with the Bethe-Salpeter approach, and find a discrepancy in the case of the 1S state. Our theoretical results are in good agreement with the available experimental data. -(3) of this reference should be s.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0
3

Year Published

1992
1992
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 17 publications
4
37
0
3
Order By: Relevance
“…In order to obtain the spectrum at order m␣ s 4 , ␣ V s has to be calculated to order ␣ s 3 ͑two loops͒, V s ͑1͒ to order ␣ s 2 ͑one loop͒, and the remaining potentials to order ␣ s ͑tree level͒. They are and the complete V s ͑2͒ have been computed over the years ͑Buchmüller et al, 1981;Gupta andRadford, 1981, 1982;Pantaleone et al, 1986;Titard and Yndurain, 1994;Pineda and Soto, 1999;Manohar and Stewart, 2000b;Kniehl et al, 2002a͒ and can be found in the article by Kniehl et al ͑2002a͒. Several comments are in order concerning these calculations.…”
Section: Potentialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to obtain the spectrum at order m␣ s 4 , ␣ V s has to be calculated to order ␣ s 3 ͑two loops͒, V s ͑1͒ to order ␣ s 2 ͑one loop͒, and the remaining potentials to order ␣ s ͑tree level͒. They are and the complete V s ͑2͒ have been computed over the years ͑Buchmüller et al, 1981;Gupta andRadford, 1981, 1982;Pantaleone et al, 1986;Titard and Yndurain, 1994;Pineda and Soto, 1999;Manohar and Stewart, 2000b;Kniehl et al, 2002a͒ and can be found in the article by Kniehl et al ͑2002a͒. Several comments are in order concerning these calculations.…”
Section: Potentialsmentioning
confidence: 99%
“…At lowest order in the weak-coupling regime ͉͑p͉ ӷ⌳ QCD ͒, the potential is Coulombic. Higherorder corrections to the potential in perturbation theory were obtained over the years ͑Buchmüller et al, 1981;Gupta andRadford, 1981, 1982;Pantaleone et al, 1986;Titard and Yndurain, 1994͒ even though the computations were difficult due to the several scales involved. It was also not clear how to systematically incorporate US effects.…”
Section: Introductionmentioning
confidence: 99%
“…(2) for calculating the hyperfine (1 1) is also the spin-independent part of the nonsingular Hamiltonian used by Gupta, Repko, and Suchyta [7] In Eq. (5), V ( p , p l ) is given by (GRS).…”
Section: Herementioning
confidence: 99%
“…Even the sign of the hyperfine splitting then changes. We also used the nonsingular Hamiltonian of Gupta, Repko, and Suchyta [7] obtained by means of the improved quasistatic approximation of Gupta [4] in a nonperturbative variational calculation to obtain the hyperfine splitting AMp of the P states. Now all the terms in the nonsingular Hamiltonian, including the spin-independent, tensor, and spin-orbit terms, contribute to the hyperfine splitting since the wave functions for the triplet and the singlet states are different in a nonperturbative variational calculation using the full Hamiltonian.…”
Section: Herementioning
confidence: 99%
See 1 more Smart Citation